Formulation and Evaluation of Hyoscine Butylbromide Parenteral Dosage Form - Mol, Bency; B. Kamath, Uday; Anusha, N. (Asian Journal of Chemistry, 2015)
A cost-effective, stable and efficacious parenteral formulation of hyoscine butylbromide, a quaternary ammonium derivative with antimuscarinic and anticholinergic activity used to relieve smooth-muscle spasm in gastro-intestinal and genito-urinary disorders, has been developed in the present study. This expensive drug is unstable in the presence of moisture, light and heat. We have investigated effect of temperature, light, pH and oxygen on the stability of drug. The drug was made into single dose-small volume injectable formulation for administration via intravenous. Formulation trails were carried out in different combinations of different buffers and excipients. Out of all the trials, the best optimized formulations which showed better stability as well as efficacy and which passed all tests satisfactorily when subjected to accelerated stability testing were finalized as commercially viable formulation.